Numerical methods for modelling the viscous effects on the interactions between multiple wave energy converters - McCallum, Peter Duncan (The University of Edinburgh, 2017)
The vast and rich body of literature covering the numerical modelling of hydrodynamic floating body systems has demonstrated their great power and versatility when applied to offshore marine energy systems. It is possible to model almost any type of physical phenomenon which could be expected within such a system, however, limitations of computing power continue to restrict the usage of the most comprehensive models to very narrow and focused design applications. Despite the continued evolution of parallel computing, one major issue that users of computational tools invariably face is how to simplify their modelled systems in order to achieve practically the necessary computations, whilst capturing enough of the pertinent physics, with great enough ‘resolution’, to give robust results. The challenge is, in particular, to accurately deliver a complete spectrum of results, that account for all of the anticipated sea conditions and allow for the optimisation of different control scenarios. This thesis examines the uncertainty associated with the effects of viscosity and nonlinear behaviour on a small scale model of an oscillating system. There are a wide range of Computational Fluid Dynamics (CFD) methods which capture viscous effects. In general however, the oscillating, six degree-of-freedom floating body problem is best approached using a linear potential flow based Boundary Element Method (BEM), as the time taken to process an equivalent model will differ by several orders of magnitude. For modelling control scenarios and investigating the effects of different sea states, CFD is highly impractical. As potential flows are inviscid by definition, it is therefore important to know how much of an impact viscosity has on the solution, particularly when different scales are of interest during device development. The first aim was to develop verified and validated solutions for a generic type decaying system. The arrangement studied was adapted from an array tank test experiment which was undertaken in 2013 by an ...